2021
DOI: 10.1016/j.ymgmr.2021.100725
|View full text |Cite
|
Sign up to set email alerts
|

The Gaucher earlier diagnosis consensus point-scoring system (GED-C PSS): Evaluation of a prototype in Finnish Gaucher disease patients and feasibility of screening retrospective electronic health record data for the recognition of potential undiagnosed patients in Finland

Abstract: Background Gaucher disease (GD) is a rare inherited multiorgan disorder, yet a diagnosis can be significantly delayed due to a broad spectrum of symptoms and lack of disease awareness. Recently, the prototype of a GD point-scoring system (PSS) was established by the Gaucher Earlier Diagnosis Consensus (GED-C) initiative, and more recently, validated in Gaucher patients in UK. In our study, the original GED-C PSS was tested in Finnish GD patients. Furthermore, the feasibility of point scoring large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…One patient was diagnosed with GD clinically and confirmed on genetic testing and one extra heterozygote was identified. Using the more comprehensive Gaucher earlier diagnosis consensus point‐scoring system which includes clinical as well as laboratory data, one study identified 42 individuals scoring >7.5 point threshold with reduced lysoGB1 (<1.2 ng/mL) but failed to identify any new cases of GD from 170 000 individuals in a Finnish biobank 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient was diagnosed with GD clinically and confirmed on genetic testing and one extra heterozygote was identified. Using the more comprehensive Gaucher earlier diagnosis consensus point‐scoring system which includes clinical as well as laboratory data, one study identified 42 individuals scoring >7.5 point threshold with reduced lysoGB1 (<1.2 ng/mL) but failed to identify any new cases of GD from 170 000 individuals in a Finnish biobank 27 …”
Section: Discussionmentioning
confidence: 99%
“…Using the more comprehensive Gaucher earlier diagnosis consensus pointscoring system which includes clinical as well as laboratory data, one study identified 42 individuals scoring >7.5 point threshold with reduced lysoGB1 (<1.2 ng/mL) but failed to identify any new cases of GD from 170 000 individuals in a Finnish biobank. 27 The strength of the PATHFINDER studies is the use of primary care samples to ensure a lack of selection bias compared to cohorts identified from secondary care clinics. The study is limited by the assumed prevalence of asymptomatic GD being lower than suggested in the literature and by the lack of clinical phenotyping data to pair with the laboratory analyses so that a more specific clinical scoring system for GD could not be used.…”
Section: Ta B L E 1 Demographic Information On Patients Recruited To the Pathfinder Gaucher Disease Studymentioning
confidence: 99%
“…We have recently introduced a novel approach for the screening of undiagnosed GD patients in Finland [ 15 ]. If successful, the approach that utilises Gaucher Earlier Diagnosis Consensus point-scoring system (GED-C PSS) [ 16 ], automated point scoring of longitudinal electronic health record (EHR) data, and Finnish biobank data and specimens allows the screening of large populations.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the Finnish EHR data of the secondary/tertiary health care and the GED-C PSS in the automated point scoring was demonstrated in our previous study assessing ca 160,000 sample donors in Auria biobank (Turku, Finland) [ 15 ]. The GED-C PSS of 32 signs/covariables, originally developed for patient chart review-based point scoring of type 1 and type 3 GD, independently from the current study, represents a prototype PSS that hasn't been assigned for a commonly accepted cut-off value but which has so far been validated in 25 UK patients as well as tested in five Finnish GD patients [ [15] , [16] , [17] ]. In the five Finnish GD type 1 patients, the GED-C point score was 6–18.5 per 28–29 manually assessed signs/covariables per patient [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation